Projeto e análise de observadores para o controle sensorless de máquinas BLDC aplicadas na tração de veículos elétricos - Rocha, Lucas Rossato (2021)
This master’s thesis presents a sensorless control of a BLDC machine for the traction of electric vehicles. Due to its characteristics, the BLDC is an excellent candidate for such application. In this context, the safety and reliability of the machine are fundamental, and it is common to use sensorless techniques as a form of redundancy in the event of a mechanical sensor failure. Therefore, first, a design methodology for a back- EMF observer based on the mathematical model of the machine that allows allocating the poles and zeros of the plant in the positions desired by the designer will be presented. Next, two existing methodologies in the literature will be studied to estimate the position and speed from the back-EMF observer: the first uses the tangent arc and state variable filter and the second uses a positive sequence detector and a phase-locked loop. Finally, the machine control will be carried out from the estimated quantities. Simulation and experimental results will validate the studies developed in this master’s thesis.